OCIAL ECONOMIC PERSPECTIVES OF SIAK RIVER COMMUNITY - Firman Nugroho (Berkala Perikanan Terubuk, 2009)
This research to tittle to people’s social-economic of side river a special area Siakriver. This area has some of the best researching, especially to relate betweensocial-economic and ecology. The collected of data is time series data from2005-2007 years and methodology is survey . Most impressive is the result,condition for people’s social-economic to shown : river and forest not supportpeople’s lives because destructed of rivers and forest; level of people’s educat islow and high of droup out in education; degree of health and infratructur ofhealth are low; the accesibility to financial in bank is low but ‘rentenir’ supportlive peoples;